Unhealthy behavior clustering and mental health status in United States college students. Issue 8 (17th November 2019) - Jao, Nancy C.; Robinson, Laura D.; Kelly, Peter J.; Ciecierski, Christina C.; Hitsman, Brian
Abstract: Objective : Examine the association of health risk behavior clusters with mental health status among US college students. Participants : 105, 781 US college students who completed the Spring 2011 National College Health Assessment. Methods : We utilized the latent class analysis to determine clustering of health risk behaviors (alcohol binge drinking, cigarette/marijuana use, insufficient physical activity, and fruit/vegetable consumption), and chi-square and ANOVA analyses to examine associations between the class membership and mental health (mental health diagnoses, psychological symptoms, and self-injurious thoughts/behaviors). Results : Three classes were identified with differing rates of binge drinking, substance use, and insufficient physical activity but similar rates of insufficient fruit/vegetable consumption. Students classified with the highest rates of binge drinking and cigarette/marijuana use had the highest rates across all mental health variables compared to other classes. Conclusions: Students who reported engaging in multiple health risk behaviors, especially high alcohol and cigarette/marijuana use, were also more likely to report poorer mental health.